Design and Optimization of a Fast Neutron Radiography System Based on a High-Intensity D-T Fusion Neutron Generator. (3rd July 2019) - Wang, Jie; Li, Yanan; Wang, Yongfeng; Li, Taosheng; Zhang, Zaodi
Abstract: A fast neutron radiography (FNR) system based on the high-intensity deuterium-tritium (D-T) fusion generator (HINEG) facility, which employs a high-intensity D-T fusion generator, was designed. To determine the optimal design of the FNR system, the influence of key parameters [the scattered neutron ratio ns (ratio of scattered neutrons and total neutrons at image detection system), collimator ratio L/D, distance between the sample and image detector t, and sample thickness d] on the spatial resolution and image contrast of the system was analyzed using the FLUKA code. The design parameters were optimized to reduce scattering and thus ensure better spatial resolution. The FNR system was constructed for HINEG according to the optimal design parameters, and FNR experiments were conducted to validate the simulation results and evaluate the actual spatial resolution. The experimental results showed that the spatial resolution of this FNR system is approximately 0.5 mm, which is in agreement with the calculation results.